The Implementation of a Servant Attitude Based on Philippians 2:5–11 - Norawanti; Hana Suparti (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
Philippians 2:5–11 is one of the most significant Christological passages in the New Testament, emphasizing the humility and obedience of Jesus Christ as the supreme model of service. In Pauline theology, ministry is not merely an external activity but an inner disposition reflected in self-emptying, prioritizing others, and glorifying God. This study aims to examine the level of implementation of a servant attitude based on Philippians 2:5–11 and to identify the most dominant dimension shaping congregational life. The research employs a quantitative approach using a survey method involving 23 respondents from the Indonesian Faithful Christian Church (GKSI) Logos Entawak Congregation. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, normality testing, confidence interval analysis, and linear regression with the assistance of SPSS 25. The findings indicate that the implementation of a servant attitude is at a moderate level. Among the analyzed dimensions, possessing a servant attitude emerges as the most dominant factor influencing the practice of humility, with a correlation coefficient of 0.880 and a contribution of 77.5%. These results affirm that the internalization of Christlike servanthood plays a crucial role in shaping sustainable and authentic Christian ministry.